Some fixed point theorem uses intimate mappings to produce intuitionistic fuzzy metric space - Ram Singh (Journal of Hyperstructures, 2024)
The aim of this research paper to use the concept of Intimate mappings to demonstrate the existence and uniqueness of common fixed point theorems for self-mappings in intuitionistic fuzzy metric space. The goal of this research work is to prove the existence and uniqueness of common fixed point theorems for selfmappings in intuitionistic fuzzy metric space using the notion of intimate mappings